2014
DOI: 10.1111/sjop.12145
|View full text |Cite
|
Sign up to set email alerts
|

Association between brain activation (fMRI), cognition and school performance in extremely preterm and term born children

Abstract: The purpose of the study was to investigate a possible association between brain activation in functional magnetic resonance imaging scans, cognition and school performance in extremely preterm children and term born controls. Twenty eight preterm and 28 term born children were scanned while performing a working memory/selective attention task, and school results from national standardized tests were collected. Brain activation maps reflected difference in cognitive skills but not in school performance. Differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 33 publications
(39 reference statements)
0
4
0
2
Order By: Relevance
“…Earlier, Griffiths et al (2013Griffiths et al ( , 2014 performed fMRI on 11-year-old extremely prematurelyborn children while they performed a combined Stroop n-back task. In line with the present study, they reported reduced activation in the preterm compared with term-born children in the prefrontal cortical areas and, in addition, in parietal areas.…”
Section: N-back Task Performance and Brain Responsivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier, Griffiths et al (2013Griffiths et al ( , 2014 performed fMRI on 11-year-old extremely prematurelyborn children while they performed a combined Stroop n-back task. In line with the present study, they reported reduced activation in the preterm compared with term-born children in the prefrontal cortical areas and, in addition, in parietal areas.…”
Section: N-back Task Performance and Brain Responsivenessmentioning
confidence: 99%
“…Few fMRI studies have investigated the neural underpinnings of WM in school-aged children and adolescents born preterm. Impaired WM in 11-year-old children born extremely preterm was associated with reduced activations in fronto-parietal areas (Griffiths et al, 2013(Griffiths et al, , 2014, whereas 13-year-old adolescents born very preterm, compared with controls, had greater activation of the WM network during manipulation of information (Arthursson et al, 2017). In a study on 7-12-year-old children, very preterm-born children activated the right middle frontal gyrus less and the superior frontal gyrus more than controls during WM performance (Mürner-Lavanchy et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Functional magnetic resonance imaging (fMRI) studies, involving tasks such as the Stroop and number estimation, have shown an association between longer gestation and more pronounced hemodynamic responses in parietal brain regions. Shorter GA has also been associated with more prefrontal cortex activity in young adults born < 37 weeks’ gestation when completing a magnitude comparison task [20], in 6- to 7-year-old children born between 27-32 weeks with a numerical distance effect task [21, 22] and 11-year-old youth born < 28 weeks’ gestation with a working memory/selective attention task [23]. As FT children mature, areas of the brain associated with performing mathematics change from mostly frontal to less frontal and more parietal areas, possibly due to procedural changes in how mathematics is performed [24, 25].…”
Section: Introductionmentioning
confidence: 99%
“…Our hypothesis was that the adolescents who had been born very preterm would show poorer performance in visual perception tasks compared with the group born full-term and that the neural activation pattern would differ between the groups, possibly due to suboptimal development of neural networks in children born very preterm. In some fMRI studies, only specific brain regions of interest selected in advance were analyzed (Gimenez et al, 2005;Griffiths et al, 2014). We chose to not limit the areas analyzed, since no previous studies with a comparable study protocol were found, and since relatively diffuse neural networks have been activated in participants born prematurely in earlier fMRI studies on cognitive processes.…”
Section: Introductionmentioning
confidence: 99%